Multiskilling in construction ‐ a strategy for stable employment - Lill, Irene (Technological and Economic Development of Economy, 2009)
After years of prosperity the construction industry is facing the current recession. This severely affects both construction companies and the workforce employed by them. The lack of skilled labour has always influenced construction outcomes, but, in the current economic environment, the problem is becoming more acute. The growth of unemployment among construction workers will cause additional social problems and does not alleviate the shortage of skilled craftsmen. A simulation model reflecting the performance of a construction firm is introduced. It enables the evaluation of different management strategies with consideration of the contradictory interests of owners, contractors and craftsmen in order to analyse the compromise and choose an appropriate solution for all parties.Gretutinės specialybės statyboje – darnaus užimtumo strategijaSantrauka. Po klestėjimo metų statybos pramonė susiduria su nūdienos recesija. Ji smarkiai veikia tiek statybos įmones, tiek jų darbo jėgą. Kvalifikuotų darbuotojų stoka visada darė poveikį statybos įmonių veiklos rezultatams, o dabartinėje ekonominėje situacijoje, problema vis labiau aštrėja. Augantis statybininkų nedarbas sukelia papildomų socialinių problemų, tačiau neišprendžia kvalifikuotos darbo jėgos stokos problemos. Sukurtas modelis, kuriuo galima imituoti įmonės veiklą. Juo galima vertinti įvairias valdymo strategijas įvertinant prieštaringus savininkų, rangovų ir darbininkų interesus ieškant kompromiso bei renkantis visoms šalims priimtiniausią variantą.Reikšminiai žodžiai: darbo jėgos valdymo strategijos, gretutinių specialybių įgijimas, darbo jėga,modeliavimas.First published online: 21 Oct 2010